Purification and characterization of pyruvate kinase from normal and tumor breast tissues - Yilmaz, S; Ozan, ST; Özercan, IH (Tubitak Scientific & Technological Research Council Turkey, 2004)
The molecular weight and kinetic properties of pyruvate kinase purified from human normal and tumor breast tissues were studied and the activity levels of pyruvate kinase from normal and tumor breast tissues were compared. The presence of 2 forms of pyruvate kinase in human breast tissue was demonstrated by DEAE Sephadex A-50 chromatography. The molecular weight of subunits estimated by SDS-PAGE in forms I. and II. in normal breast tissue and in forms I. and II. in tumor breast tissue were .30,000 and 63,000 Da and 16,500 and 60,000 Da, respectively. It was found that the pyruvate kinase activity in tumor tissue was 5.2 times higher than that in normal tissue. Peaks I and II of pyruvate kinase were able to be purified about 1591-fold and 636.4-fold in normal breast tissue, and 219-fold and 318-fold in tumor breast tissue, respectively. The reaction rate curve was hyperbolic in the first peaks of both normal and tumor breast tissue pyruvate kinase and was not activated by fructose-1, 6-diphosphate (FDP). Reaction rate curves in the second peaks of tumor breast tissue and normal breast tissue pyruvate kinase were hyperbolic and sigmoidal, respectively, and were activated by FDP. The Hill coefficient showed that there were at least 2 binding regions in the enzyme for PEP. When compared with other tissue pyruvate kinase isozymes, it seems likely that the isoenzymes of pyruvate kinase isolated from human breast tissue were M-1 and M-2 isozymes and that the M-2 isozyme of pyruvate kinase from normal breast tissue changed into K isoenzyme in tumor breast tissue.
Pirüvat kinazin normal ve tümör meme dokusundan saflaştirilmasi ve karakterizasyonu
Keywords: human breast tumour; pyruvate kinase; purification; kinetic properties